Magnetic Resonance Imaging-Guided Surgical Design: Can We Optimize the Fontan Operation? - Haggerty, Christopher M. (Cardiol Young, 2013)
The Fontan procedure, although an imperfect solution for children born with a single functional ventricle, is the only reconstruction at present short of transplantation. The hemodynamics associated with the total cavopulmonary connection, the modern approach to Fontan, are severely altered from the normal biventricular circulation and may contribute to the long-term complications that are frequently noted. Through recent technological advances, spear-headed by advances in medical imaging, it is now possible to virtually model these surgical procedures and evaluate the patient-specific hemodynamics as part of the pre-operative planning process. This is a novel paradigm with the potential to revolutionize the approach to Fontan surgery, help to optimize the hemodynamic results, and improve patient outcomes. This review provides a brief overview of these methods, presents preliminary results of their clinical usage, and offers insights into its potential future directions.